2013
DOI: 10.4103/0019-5154.110890
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous metastasis of neuroendocrine carcinoma

Abstract: The skin is a relatively uncommon site for distant metastatic deposits, compared with organ such as liver, bone, and lung. The most common sources of cutaneous metastases are: Breast, lung, colon, stomach, upper aeridigestive tract, uterus and kidney

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Here, we reported a case of a small-cell rectal NEC with a very uncommon, subcutaneous tissue metastatic site. Cutaneous metastases are more commonly present in breast, lung, colon, stomach, uterus and kidney neoplasia [57], while spread to the skin is infrequent in neuroendocrine carcinomas and need to be differentiated from primary neuroendocrine skin tumors, in particular from Merkel cell carcinoma [58–60]. A review conducted by Amorim et al in 2015 [11] found 31 cases of cutaneous metastases of NET.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we reported a case of a small-cell rectal NEC with a very uncommon, subcutaneous tissue metastatic site. Cutaneous metastases are more commonly present in breast, lung, colon, stomach, uterus and kidney neoplasia [57], while spread to the skin is infrequent in neuroendocrine carcinomas and need to be differentiated from primary neuroendocrine skin tumors, in particular from Merkel cell carcinoma [58–60]. A review conducted by Amorim et al in 2015 [11] found 31 cases of cutaneous metastases of NET.…”
Section: Discussionmentioning
confidence: 99%
“…[15]3 cases of soft tissue sarcomas that had metastases to skin ans subcutaneous tissue were identified in 3 females .The histological types were epitheloid sarcoma, leiomyosarcoma and rhabdomyosarcoma .Metastases occured to interscapular area and abdominal wall .The diagnosis was established by FNAC.2 cases of metastaic neuroendocrine carcinoma were seen in our series .One patient had primary in salivary gland and the other presented with metastases in sacral area.Patient on follow up was found to have neuroendocrine carcinoma prostrate .Cutaneous metastases from neuroendocrine carcinoma of visceral organ has already been reported .When a neuroendocrine carcinoma is found in the skin ,it is importantto distinguish Merkel cell carcinoma from cutaneous metastases of visceral origin.Positive staining for CK20 is strongly diagnostic. [17]The diagnosis was confirmed by a complete IHC study of both primary and secondary lesions. Cutaneous metastases of an extracutaneous NHL seems to be poor prognostic factor.…”
Section: Resultsmentioning
confidence: 95%
“…The location was most frequently on the cephalic segment (typically on the scalp) and/or trunk. We call attention to two distinct cases: (1) painful spots referred by the patient without visible or palpable cutaneous lesions; (2) single hardened lesion on the eyelid, simulating the primary cutaneous lesion [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%